2020
DOI: 10.5114/pq.2020.96234
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between shock wave therapy and mechanical massage for the treatment of cellulite in women

Abstract: IntroductionTo evaluate the effects of shock wave therapy on the fibrous septa of cellulite in Brazilian womenMethodsThe sample consisted of 20 women with gluteal cellulite (grade III) evaluated through protocols and ultrasound examinations before and after treatment. The volunteers were randomly distributed into treatment group (TG) and control group (CG). TG received shock wave therapy, while CG volunteers received vibratory massage. The shock wave parameters were: intensity of 3.5 bar, frequency of 21 Hz, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The possibilities of using and the positive effect of vibratory massage systems on the appearance of the strings in women with GLD were also presented in the study results by Adatto et al 33 and Sadowski et al 34 The study by Chieregato et al demonstrated the advantages of oscillatory vibrotherapy on body contours and skin tightness. 35 The study by Maia et al 36 showed a positive local effect of shock wave therapy in reducing the thickness of the fatty layer and the number of cellulite septa in the posteriors of women with GLD.…”
Section: Discussionmentioning
confidence: 99%
“…The possibilities of using and the positive effect of vibratory massage systems on the appearance of the strings in women with GLD were also presented in the study results by Adatto et al 33 and Sadowski et al 34 The study by Chieregato et al demonstrated the advantages of oscillatory vibrotherapy on body contours and skin tightness. 35 The study by Maia et al 36 showed a positive local effect of shock wave therapy in reducing the thickness of the fatty layer and the number of cellulite septa in the posteriors of women with GLD.…”
Section: Discussionmentioning
confidence: 99%